O lugar do leitor na poesia de Manoel de Barros - BARROS, Nismária Alves David (2010)
This thesis studies work by poet Manoel de Barros, published between 1937 and 2008, to know and to detail the procedures that delineate the reader s place and that promote the readability of his poems. Investigate how the poetic discourse by Barros builds the reception of his texts is a contribution to the field of Brazilian studies of contemporary poetry and it is in search s line "Poetics of Modernity". At first this research is based on the concept of reader as a textual construction from the theory of Model-Reader by Umberto Eco. Then it is considered the role of poetry is communication, according to theoretical assumption by Michael Hamburger, because the poetry communicates the art and the man. Eventually this research discusses the eroticism related to poetic creation, essentially based on meanings of eroticism by Octavio Paz as body poetic as verbal eroticism. Considering this theoretical support and others citations in analysis of selected poems, we can identify in poetry by Manoel de Barros, for example, the performative act in the metalinguistic discourse, the invention of a lyrical subject as poet, the indication of an interlocutor in the text, the memory of reading, the experience lived, the use of irony as paradox and the eroticism. The results confirm that the emphasis on reading is a key element in poetic construction by Barros. This writer modernizes and renews the modern experience of poetry because he communicates the historical experience in order to organize and master his poetic materials. When Barros makes poetry, he makes the subject and the reader, he shares his poetic values with the reader, he incentives the reader to think about itself and the world, he offers his greatest contribution, which is the appreciation of poetry, and he invites the necessary humanity of the man.